Impact! – Bolides, Craters, and Catastrophies - Reimold, W.; Jourdan, Fred (Mineralogical Society of Canada, 2012)
It is now universally accepted that the impact of planetesimals, asteroids, and comets has been a fundamental process throughout the Solar System. Catastrophic impact events have been instrumental in developing the early history of the planets and have caused environmental disasters throughout Earth history. A major mass extinction at the Cretaceous–Paleogene boundary has been confidently related to an impact event (Chicxulub, Mexico). While the study of impact cratering is a multidisciplinary field, mineralogical and geochemical investigations have been central since the beginning, focusing on the nature of impact-generated rocks and of the extraterrestrial projectiles and their interaction with geological materials. Chemical and isotopic techniques have allowed the dating of impact events and the identification of traces of meteoritic projectiles in impact-formed rocks on Earth and the Moon.